Eighteen month follow up of Helicobacter pylori positive children treated with amoxycillin and tinidazole. Issue 10 (October 1992) - Oderda, G; Vaira, D; Ainley, C; Holton, J; Osborn, J; Altare, F; Ansaldi, N
Abstract : Sixty three children with dyspepsia (mean age 12 years, range one to 18, M/F 41/22) were Helicobacter pylori positive by histology of gastric antral biopsy specimens and were treated with a six week course of amoxycillin (50 mg/kg) and tinidazole (20 mg/kg). The endoscopic diagnoses were: normal (16), nodular gastritis (19), oesophagitis (four), duodenal ulcer (13), and gastric ulcer (11). H pylori was eradicated in 54 (87%) and histological gastritis resolved in 51 and was improved in the other three. Repeat investigation was offered at six monthly intervals. Reinfection was found in three of 34 (9%) at six months, in none of 22 at 12 months, and in two of 18 (11%) at 18 months, yielding an 18 month cumulative relapse rate of 20%. Children with persisting infection despite treatment remained positive during follow up. Serum H pylori IgG concentrations fell after treatment (p < 0.001), and for individual children during follow up there was a progressive decline, but an increased concentration indicated recurrence. After eradication of H pylori by combined amoxycillin and tinidazole treatment, only a minority of children relapse during the ensuing 18 months.